2021
DOI: 10.1177/10547738211033917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupressure and Abdominal Massage on Constipation in Patients with Total Knee Arthroplasty: A Randomized Controlled Study

Abstract: This study was a randomized controlled trial aimed to compare the effects of acupressure and abdominal massage on constipation development for patients with TKA. The patients were randomly assigned to each group: control group ( n = 31), acupressure group ( n = 30), and abdominal massage group ( n = 30). The finding showed that the severity of constipation and straining stool consistency of the groups in which acupressure and abdominal massage was applied are significantly better than the control group ( p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The results showed stool consistency had improved after acupressure and abdominal massage, but unlike in our study, the patients in the intervention group defecated earlier than the others. 27 Similar to our study, another study revealed significant improvement in constipation symptoms among advanced cancer after three sequences of day intervention. The last study, similar to ours, used ST25 acupressure point, but unlike our study, the researchers used multiple laxatives such as sennoside, magnesium oxide, primperan, lactulose, bisacodyl, Dulcolax suppositories, and glycerin enema.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed stool consistency had improved after acupressure and abdominal massage, but unlike in our study, the patients in the intervention group defecated earlier than the others. 27 Similar to our study, another study revealed significant improvement in constipation symptoms among advanced cancer after three sequences of day intervention. The last study, similar to ours, used ST25 acupressure point, but unlike our study, the researchers used multiple laxatives such as sennoside, magnesium oxide, primperan, lactulose, bisacodyl, Dulcolax suppositories, and glycerin enema.…”
Section: Discussionsupporting
confidence: 89%
“…Both the frequency of distension and constipation were decreased with abdominal massage. In addition, Durmuş skender and alşkan [39] , who studied the effects of massage on constipation, found that it alleviated the pain of constipation and sped up the first time the patient went. Yet, when constipation sets in, doctors often prescribe laxatives or enemas, which can be unpleasant for patients, make them reliant on others, disrupt their body's liquidelectrolyte balance, drive up healthcare costs, and add more work for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of functional constipation in China is about 6% [ 4 ]. Chronic constipation not only reduces the quality of life of patients and causes problems in the genitourinary system, circulatory system, nervous system, and other systems [ [5] , [6] , [7] ], but also poses a significant physical and psychological risk to patients [ 8 ]. Due to the long treatment period, multiple causes of constipation, poor clinical efficacy, recurrent symptoms, and difficulty in eradicating constipation, a large number of medical resources are used [ 9 ].…”
Section: Introductionmentioning
confidence: 99%